The Impact of Emergency Department Process Optimization Combined With Health Education on the Treatment Outcomes and Anxiety and Depression in Patients With Acute Ischemic Stroke. - Xie, Xiaodong; Wang, Shouzhang; Zhang, Mingying; Tang, Lifen (Actas Espanolas de Psiquiatria, 2026)
Background: To explore the association between an optimised emergency procedure combined with structured health education and anxiety, depression and treatment outcomes in patients with acute ischaemic stroke (AIS). Methods: We conducted a retrospective cohort study of 114 AIS patients admitted to our stroke centre between January and December 2023. On the basis of the admission timeframe, patients were divided into a conventional care group (n = 57, January to June 2023, routine care) and a comprehensive nursing group (n = 57, July to December 2023, optimised integrated care). Emergency nursing outcomes were assessed after stabilisation and before ward transfer. Neurological recovery was assessed with the European Stroke Scale (ESS); anxiety and depression were assessed with the Generalized Anxiety Disorder-7 (GAD7) and Patient Health Questionnaire-9 (PHQ-9) as primary psychological indicators. Process times and nursing satisfaction were also evaluated. Data analysis was conducted using SPSS 27.0. Normality was verified using the Shapiro-Wilk test. Normally distributed data were expressed as mean ± standard deviation and analysed using an independent samples t-test, whereas non-normal data were expressed as median (interquartile range) and analysed using the Mann-Whitney U test. Categorical data were analysed using chi-square test. Multivariate linear and logistic regression were used to analyse indicators such as neurological function and nursing satisfaction, adjusting for confounding factors. A p-value < 0.05 was considered statistically significant. Results: Compared with the conventional care group, the waiting time, diagnosis time, emergency room waiting time and recanalisation time of patients in the comprehensive nursing group were significantly shortened (p < 0.05). The degree of improvement in ESS (∆ESS) in the comprehensive nursing group was significantly higher, and the reductions in GAD-7 and PHQ-9 scores were also significantly greater (p < 0.05). Patient and family satisfaction in the comprehensive nursing group were significantly higher than those in the conventional care group (p < 0.05). Through multivariate linear regression analysis, with baseline National Institutes of Health Stroke Scale (NIHSS) score, time from onset to visit, hypertension and diabetes as adjustment factors, allocation to the comprehensive nursing group was still significantly correlated with ∆ESS (β [95% confidence interval (CI)] = 8.15 [5.72 to 10.58], p < 0.001), ∆GAD-7 (β [95% CI] = −2.18 [−2.92 to −1.44], p < 0.001), and ∆PHQ-9 (β [95% CI] = −2.65 [−3.32 to −1.98], p < 0.001). The results of multivariate logistic regression analysis showed that, after adjusting for the above confounding factors, inclusion in the comprehensive nursing group was independently associated with a significantly higher likelihood of obtaining a satisfactory nursing evaluation (adjusted OR = 8.915, 95% CI: 2.453 to 32.468, p = 0.001). Conclusions: The integrated model is associated with shorter treatment times, better neurological recovery, reduced anxiety and depression and higher satisfaction in AIS patients, providing preliminary evidence for a patientcentred comprehensive emergency care model.